Electro-Optical Modulator Requirements for 1 Tb/s per Channel Coherent Systems - Rossi,Sandro Marcelo (2021)
Abstract The electro-optical bandwidth and extinction ratio requirements of in-phase and quadrature modulators to enable 1 Tb/s per channel optical transmission rates are evaluated through numerical simulations. Employing sixty-four quadrature amplitude modulation (64QAM), the simulation results indicate that the best trade-off between the number of optical carriers per channel and the technological complexity of designing and manufacturing an integrated transceiver is achieved for a superchannel composed by 2 optical carriers, since it allows modulator requirements in terms of electro-optical bandwidth and extinction ratio equal to 27 GHz and 18 dB, respectively. The systemic optimization of the carrier launch power employing the approximate enhanced Gaussian noise model indicates that this configuration could achieve transmission reaches up to around 1080 km. These results point out to 1 Tb/s optical superchannels as a viable solution for next generation coherent systems in metropolitan and long-haul scenarios.